Near-infrared spectroscopy of the cerebellum in motor activation tasks - Yew Long Lo; Gerald Teck Heng Chia; Yan Teng Celeste Chen; Eng King Tan (Scientific Reports)
Abstract Near-infrared spectroscopy (NIRS) is a non-invasive modality for evaluating neurovascular coupling in the cerebellum during motor tasks with good temporal resolution. However, previous attempts to measure cerebellar activity with NIRS were limited and did not utilize validated tasks for bedside clinical testing. We employed 2 clinical tasks intended to closely engage the cerebellar and corticospinal systems within an environment which eliminated confounding visual and sound stimuli. Task 1 is a well-recognized bedside maneuver to assess a fundamental cerebellar function, and correspondingly, Task 2, for corticospinal motor activity. Subjects were tested with Protocols 1 and 2. Protocol 1 consisted of 5 optodes (4 sources and 1 detector, 4 recording channels) spaced 3 cm apart and comprising single-tipped LED light sources in conjunction with single-tipped fiber-optic detectors. Protocol 2 consisted of 10 optodes (2 sources and 8 detectors, 8 recording channels) spaced 2 cm apart and comprising single-tipped LED light sources in conjunction with dual-tipped fiber-optic detectors. Protocol 2 had detected increased neurovascular coupling activity above and beyond any inherent corticospinal activity in the cerebellum when Task 1 was performed compared to when Task 2 was performed. In addition, stable recordings were obtained in 100% of patients using Protocol 2 compared to only 50% with Protocol 1. Our study has demonstrated the enhanced feasibility and superiority of NIRS for evaluating neurovascular coupling in the cerebellum during a cerebellum-activating motor task, both qualitatively and quantitatively, using Protocol 2 compared to Protocol 1.